Factibilidad de la utilización de aceite a partir de residuos del eviscerado de pollo en dietas para gamitana (Colossoma macropomum) - Olivares-Zamora, Cristina (2025)
The study aimed to determine the feasibility of using oil from chicken evisceration waste in diets for tambaqui fingerlings. One hundred and twenty fish with an initial average length and weight of 8.77 ± 0.4 cm and 13.2 ± 2.0 g were randomly distributed in 12 180 L aquaria, fed for 60 days with diets containing three percentages of oil (0.25, 0.5 and 1%) and compared with a control feed. Fish were extracted biweekly, and data were obtained on length, weight, specific growth rate (TCE), condition factor (K), mortality percentage, apparent feed conversion ratio (FCA), and protein efficiency ratio (PER). The results showed that at 15 and 30 days, the weight, TCE, and PER of fish fed 0.5 and 1% chicken oil did not differ statistically from the control. Similarly, at 30 days, no differences were found in FCA. Length and K were similar throughout the study between treatments. It is concluded that replacing conventional oil with oil from chicken evisceration waste in diets for tambaqui is feasible.